Kepemimpinan Ideal dalam Perspektif Pendidikan Islam - Khoirunnisa, Jany Fitria; Nurjanah, Aswin; Setiawan, Farid (ANWARUL, 2023)
Being a leader will be held accountable, at least that is to lead himself or to lead others. Does not discriminate between race, ethnicity, nation, or class. The word leader in the perspective of Islamic education has several words, namely khilafah and imam. Khilafah which means successor, heir, who is in front, followed in his footsteps both in words and deeds. While the word priest is defined as a husband and is also exemplified by the prophet Abraham as a leader for his people. Who commands in virtue and helps those who are weak as Allah has taught his people. In writing this article using the method of literature study approach. This approach is taken in collecting data from articles, journals, and others related to the theme of this article. Of course to know what ideal leadership looks like in the perspective of Islamic education as a reference.